Impact of influenza infection on the short- and long-term health of patients with chronic obstructive pulmonary disease. (31st December 2022) - Wallick, Chris; To, Tu My; Korom, Stephan; Masters, Henry; Hanania, Nicola A.; Moawad, Dalia
Abstract: Background: Influenza is a common cause of acute respiratory infection that leads to exacerbation of underlying chronic obstructive pulmonary disease (COPD). To elucidate the short- and long-term effects of influenza in patients with COPD, we examined health care resource utilization (HRU) and costs up to 13 months following influenza infection. Methods: We conducted a retrospective cohort study using U.S. insurance claims data from MarketScan. Patients with an influenza diagnosis during the 2012–2014 influenza seasons and continuous enrollment in a health plan from 12 months before to 13 months after the index influenza diagnosis were identified and propensity score–matched 1:5 to controls without evidence of influenza. COPD- and pneumonia-related outcomes were assessed over 13 months following influenza diagnosis. Results: COPD-associated outcomes after diagnosis were significantly worse in patients with influenza ( n  = 7, 087) vs. controls ( n  = 35, 435) during the first month (exacerbation: 16.1 vs. 3.4%; outpatient visits: 57.1 vs. 35.2%; emergency department (ED) visits: 10.5 vs. 1.8%; and inpatient visits: 5.6 vs. 0.7%) and months 2–13 (exacerbation: 25.1 vs. 21.1%; outpatient visits: 86.1 vs. 85.8%; ED visits: 20.0 vs. 15.7%; and inpatient visits: 6.5 vs. 5.3%). COPD- and pneumonia-associated costs for months 1 and 2–13 were higher in patients with influenza. Limitations: The study was subject to a residual imbalance between cohorts despite propensity score matching. The use of diagnostic codes to select patients and identify complications could introduce inaccuracies in estimating events. Conclusions: HRU and costs were higher in COPD patients with influenza during the first month and over the entire year following infection. This suggests influenza has an impact on respiratory health in patients with COPD that lasts beyond the acute infection.